Joint relay and jammer selection for secure cooperative networks with a full‐duplex active eavesdropper. Issue 6 (1st April 2020) - Zhou, He; He, Dongxuan; Wang, Hua
Abstract : In this study, the authors investigate the secure transmission of a cooperative network, in which a source communicates with a destination via multiple cooperative nodes in the presence of a full‐duplex active eavesdropper, which can intercept the confidential signals and transmit jamming signals simultaneously. To safeguard the security of legitimate communication, two joint relay and jammer selection schemes are proposed according to the availability of the eavesdropper's channel state information, namely, optimal relay and random jammer selection scheme and optimal relay and optimal jammer selection scheme. The authors first derive the exact closed‐form expressions of the secrecy outage probability (SOP) for different selection schemes. Aiming at minimising SOP, they then adopt the deep feedforward neural network to determine the optimal power allocation between the selected relay and jammer. Further, the asymptotic expressions for SOP in the high signal‐to‐noise ratio regime are derived. Numerical results verify the analysis and demonstrate the performance advantage of the proposed scheme over conventional relay selection scheme with optimal power allocation.